2023
DOI: 10.3390/disabilities3020017
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of People with Mild to Moderate Cognitive Impairment and Their Caregivers about Physical Activity and Exercise for Fall Prevention: A Qualitative Study

Abstract: Older adults with cognitive impairment are at high risk of experiencing falls. Although no specific fall prevention guidelines presently exist for this population, exercise programmes to prevent falls are recommended. Limited literature exploring what older adults with mild to moderate cognitive impairment think about or how they make sense of the need for such programmes exists. This study explored the perspectives of older adults with mild to moderate cognitive impairment and their caregivers about exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In our previous qualitative study [21], we found that older adults with mild to moderate cognitive impairment and their care partners had complex and changing perceptions about exercise and physical activity. The people we interviewed seemed to fluctuate between states of acceptance, denial, and accommodation, and each state would impact participants' decisions to exercise or be physically active and what sort of physical activity they wished to engage in.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In our previous qualitative study [21], we found that older adults with mild to moderate cognitive impairment and their care partners had complex and changing perceptions about exercise and physical activity. The people we interviewed seemed to fluctuate between states of acceptance, denial, and accommodation, and each state would impact participants' decisions to exercise or be physically active and what sort of physical activity they wished to engage in.…”
Section: Introductionmentioning
confidence: 85%
“…Our previous qualitative study identified three dispositions where people with mild-to-moderate cognitive impairment appeared to fluctuate between-acceptance, denial, and accommodation. Each of these states appeared to self-impact, in the moment, an individual's decision to exercise or be physically active and what sort of physical activity to engage in [21]. This apparent fluctuating nature of the early stages of dementia may be one reason people may not be inclined to participate in studies or activity programmes.…”
Section: Strength and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation